2008
DOI: 10.1183/09031936.00074207
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium complex disease: prognostic implication of high-resolution computed tomography findings

Abstract: To evaluate the prognostic implications of computed tomography (CT) findings in assessing responses to treatment in Mycobacterium avium complex (MAC) pulmonary disease without underlying lung disease, high-resolution (HR)CT findings were correlated based on the results of sputum conversion after anti-MAC therapy.A total of 59 patients underwent HRCT before treatment and the therapeutic efficacy was evaluated by the results of sputum conversion.Atelectasis, cavities and pleural thickening on HRCT were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 17 publications
2
37
1
8
Order By: Relevance
“…24 Koh ve ark., MAC'ye bağlı akciğer hastalığında nodüler bronşektazi formunun %52, üst lob kavite formunun ise %42 oranında tespit edildiğini bildirmiştir. 25 Bizim çalışmamızda hastaların radyolojik incelemesinde 27 (%64,3) hastada bilateral lezyonlar ve göğüs radyografisinde en sık olarak kavite (%64,3), segmenter veya subsegmenter homojen opasiteler (%57,8) ATS ve BTS, tedaviye yanıtsız olan veya nük-seden olgularda ilaç duyarlılık testinin yapılmasını önermektedir.…”
Section: Discussionunclassified
“…24 Koh ve ark., MAC'ye bağlı akciğer hastalığında nodüler bronşektazi formunun %52, üst lob kavite formunun ise %42 oranında tespit edildiğini bildirmiştir. 25 Bizim çalışmamızda hastaların radyolojik incelemesinde 27 (%64,3) hastada bilateral lezyonlar ve göğüs radyografisinde en sık olarak kavite (%64,3), segmenter veya subsegmenter homojen opasiteler (%57,8) ATS ve BTS, tedaviye yanıtsız olan veya nük-seden olgularda ilaç duyarlılık testinin yapılmasını önermektedir.…”
Section: Discussionunclassified
“…We read with interest the article by KUROISHI et al [1], in which the group pleasantly documented the prognostic implications of high-resolution computed tomography (HRCT) findings in Mycobacterium avium complex (MAC) disease. KUROISHI et al [1], found that the presence of atelectasis, cavities, pleural thickening or bronchiectasis on a computed tomography (CT) scan indicated poor prognosis and concluded that CT findings are good predictors of the response to treatment in MAC disease patients.…”
Section: To the Editorsmentioning
confidence: 99%
“…KUROISHI et al [1], found that the presence of atelectasis, cavities, pleural thickening or bronchiectasis on a computed tomography (CT) scan indicated poor prognosis and concluded that CT findings are good predictors of the response to treatment in MAC disease patients. However, there are a few practical issues regarding the topic that need to be addressed.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by ALDINGTON et al [1] entitled ''Cannabis use and risk of lung cancer: a case-control study''. However, we are concerned that the conclusion stating that ''long-term cannabis use increases the risk of lung cancer in young adults'' is inadequately supported by the data, given the study's several methodological flaws.…”
Section: To the Editorsmentioning
confidence: 99%